Effect of Heating Temperature, Holding Time and Stabilization Temperature on the Al-Foam Properties - Puspitasari, Dewi; Puspitasari, Poppy; Mustapha, Mazli; Ginta, Turnad Lenggo (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
The interest in metallic foam is increasing since their cellular structures have a unique combination of properties such as high stiffness, low density, lightweight, high specific strength, and thermal insulation. Commonly, the performance of metallic foam can be improved by the heat treatment process. However, the previous heat treatment methods still present the brittle crack path and the research on heat treatments of the metal foam properties is very limited. In this study, individual parameters in stress relieving treatment that contribute to Al-Foam properties were investigated. The stress-relieving process of the samples was performed using a vacuum furnace. The composition of aluminium foam was determined by X-Ray Fluorescence (XRF). The hardness test was conducted using a microhardness tester. Quasi-static compression test was conducted by a universal testing machine. From the SEM-EDX elemental images, it can be observed that traces of Ca, Fe, Ti, and Si have a homogeneous distribution in the Al-matrix. In the result obtained, the mechanical properties of aluminium alloy foam decrease when the heating temperature is enhanced. The mechanical properties of closed-cell aluminium alloy increase with the reduction of the holding temperature. This was due to the recovery and recrystallization process which depended on time and temperature during the heat treatment process. The mechanical properties of aluminium foam were raised after increasing the stabilization temperature. This finding was due to the vibrational atomic motion in the recovery process.